Efektifitas Pemusnahan Judi Online Pada Kalangan Remaja Hingga Dewasa - Farhan Tri Cesar; Natasya Desy Safitri; Ferio Aditya Rachman (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
The aim of this research is to determine differences in perceptions or characteristics between two groups of respondents as measured through questionnaires. Descriptive statistics were used to conduct this analysis. The results of the analysis showed that there were big differences between the two groups. The variance of the first group reached 220.5045 compared to 50.80424 in the second group. The first group has an average of 36.14423 with a minimum value of 18 and a maximum of 48, and a standard deviation of 7.127709, which shows relatively homogeneous data. The second group had a mean of 75.30048 with a minimum value of 37.5 and a maximum of 100, and a standard deviation of 14.84939, which shows a greater level of data diversity. These differences in features indicate that the variables affect the two groups differently. Consequently, different methods are used to explain the results. This study provides important insights into the variability in survey data between groups, which helps social research and management understand the diverse characteristics of respondents.